Conservation, collaboration, and claims: Saemie inclusion and influence in a Swedish national park process - Flodén, Linn; Reimerson, Elsa (Frontiers in Conservation Science, 2023)
In Sweden, environmental governance and management has historically been centralized, with low levels of local influence and control. Although a large proportion of the areas set aside for environmental protection in Sweden are located in Saepmie, the traditional lands of the Saemie people, Saemie influence in the governance and management of these areas has been limited. However, recent events and ongoing processes indicate a potential change in both discourse and policy practice. This paper critically examines the planning process for a proposed national park in the southern part of the Swedish mountain range. It was organized in a collaborative and participatory form, including Saemie representatives on both local and central levels. After several years of planning, local Saemie opposition to the park led to the termination of the process. We investigate discursive constructions of the local Saemie actors’ inclusion in the process and their effects on possible Saemie influence. Our results show that state and Saemie actors articulate inclusion in different ways, limiting and enabling varying forms of influence. The landscape and the state of nature were central constructions affecting the process, and the project’s aim transformed over time – with significant consequences for the process and, possibly, also its results.